Vaccine bidding, procurement and distribution management practices in mainland China: A nationwide study. Issue 52 (20th December 2021) - Wang, Wei; Wang, Yanhuan; Wang, Ying; Yan, Fei; Wang, Na; Fu, Chaowei
Abstract: Objective: To conduct a nationwide evaluation of vaccine bidding, procurement and distribution management for understanding and improving the current situation well in mainland China. Methods: An institution survey was carried out to collect information on tendering, procurement, distribution and related issues to vaccines by structured questionnaires administered to 31 provinces in mainland China from April to July 2019. Results: In 13 (41.9%) of 31 provinces, centralized bidding of National Immunization Program (NIP) vaccines was accomplished, and others conducted independent tendering and purchasing in 2018. For non-NIP vaccines, all provinces implemented unified bidding at the provincial level and over half (18, 58.1%) of them chose provincial public resource trading platforms, but their modes varied over provinces. Then procurement was undertaken by the district-level centers for disease control and prevention (CDC) while they were unable to choose the best option of too many vaccines targeted by the province-level CDC for local populations. The distribution modes of NIP and non-National Immunization Program (non-NIP) vaccines were similar overall in a province but very different over provinces. Main mode was that CDCs at different levels delivered about two thirds (64.5%) of NIP vaccines distribution and more than one third (35.5%) of non-NIP vaccines. Another distribution mode was occupied as fully buying the service from third parties in 3 municipalities. Some provinces mixed both modes, too. The total distribution volume of vaccines was 430.7 million doses in 2018. The top five non-NIP vaccines delivered in 2018 were human rabies vaccine, varicella vaccine, EV71 hand foot mouth disease vaccine, hepatitis B vaccine and influenza vaccine. Conclusion: The vaccine biding, procurement and distribution management varied over provinces in mainland China in 2018, especially for non-NIP vaccines. Specific policies and measures should be developed for different regions to improve the immunization management better.